Manajemen Pendidikan Agama Islam di Masjid Nurul Huda Pasar IV Kelambir lima - Rambey, Mustafain; Setiawan, Hasrian Rudi (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This research was conducted with the aim of knowing the management of the Islamic religious education program at the Nurul Huda Mosque Pasar IV Kelambir Lima. This research uses qualitative methods with field research. The techniques used to obtain data are interviews, observation and documentation. Meanwhile, the data analysis technique used in this research uses the Miles and Huberman data analysis model, which consists of several steps, namely: 1) Collecting Data; 2) Reduction Data; 3) Display Data; 4) Conclusions and Verifying Data. Meanwhile, the technique for ensuring the validity of the data used in this research uses triangulation, both source, technique and time triangulation. The research findings from this study are that the management of the Islamic religious education program at the Nurul Huda Mosque Pasar IV Kelambir Lima is carried out through several stages starting from activities 1) Planning, 2) Organizing, 3) Actuating, 4) Controlling, 5) Evaluation. All of these stages are carried out with the aim of ensuring that the Islamic religious education program can run well.